Dynamic screen monitoring and mouse controlling over local area network - 264396 Lim, Guey Long (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1999